2010
DOI: 10.1039/b926542b
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism for C–H bond activation in ethylene in the gas phase vs. in solution – vinylic or agostic? Revisiting the case of protonated Cp*Rh(C2H4)2

Abstract: When Cp*Rh(C(2)H(4))(2)H(+) (2) is exposed to C(2)H(4) in the gas phase, inside the cell of an FT-ICR mass spectrometer, the most notable feature is the lack of any bimolecular reactivity. Collisional activation of 2 leads to ethylene loss and formation of Cp*Rh(C(2)H(4)-mu-H)(+) (3). In contrast to the reactivity of 2 in solution, ethylene dimerisation is negligible in the gas phase. Coordinatively unsaturated 3, rather than 2, is the major species in which reactivity is observed to occur. Compound 3 reacts w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 72 publications
0
12
0
Order By: Relevance
“…Overall, our M06 energies and structures are similar to Hall's and Tilset's previous structures (Figure 1b). 2,5 Relative to 1Rh, our estimate for the G ‡ for TS1Rh is 5.5 kcal/mol and 2Rh is 5.4 kcal/mol. At -80 C these structures have nearly identical Gibbs energies.…”
Section: Results and Discussion Static Dft Energy Landscapesmentioning
confidence: 69%
See 1 more Smart Citation
“…Overall, our M06 energies and structures are similar to Hall's and Tilset's previous structures (Figure 1b). 2,5 Relative to 1Rh, our estimate for the G ‡ for TS1Rh is 5.5 kcal/mol and 2Rh is 5.4 kcal/mol. At -80 C these structures have nearly identical Gibbs energies.…”
Section: Results and Discussion Static Dft Energy Landscapesmentioning
confidence: 69%
“…2,3 Experiments and DFT calculations have demonstrated that an agostic C-H-to-metal interaction likely occurs prior to and after -hydrogen transfer. [4][5][6][7][8] Scheme 1. a) Outline of two-step and one-step -hydrogen-to-ethylene transfer reaction mechanisms. b) Qualitative energy landscape for the two-step sequence of -hydrogen elimination with a metal-hydride intermediate followed by migratory insertion.…”
Section: Introductionmentioning
confidence: 99%
“…We chose to focus our direct dynamics study on the β-hydrogen transfer reaction of [Cp*Rh III (Et)­(ethylene)] + (and Ir and Co analogues) because previous static DFT calculations showed that this Rh reaction has a two-step β-hydrogen transfer energy landscape (Figure ). , …”
Section: One Step Two Steps or Something In Between?mentioning
confidence: 65%
“…We chose to focus our direct dynamics study on the β-hydrogen transfer reaction of [Cp*Rh III (Et)-(ethylene)] + (and Ir and Co analogues) because previous static DFT calculations showed that this Rh reaction has a two-step βhydrogen transfer energy landscape (Figure 6). 48,49 After confirming the two-step potential energy landscape with the M06 functional, quasiclassical trajectories commencing from the β-hydrogen transfer transition state (TS1Rh; Figure 6) revealed complete dynamical skipping of the Rh−H intermediate. 50 Figure 7a shows 3D depictions of time snapshots of a representative dynamically ballistic Rh trajectory.…”
Section: One Step Two Steps or Something Inmentioning
confidence: 75%
“…[49][50][51][52][53] The Uggerud group investigated the mechanism for C-H bond activation of ethylene by 18e − Rh(III) and 16e − Rh(III) complexes inside the ICR cell in which H 2 elimination was observed in the reaction of ethylene and Cp-Rh(C 2 H 4 -μH) + complexes. 54 DFT calculations showed that vinylic C-H bond activation is an energetically unfavorable process. Rather, it was shown that vinylic C-H activation is possible if a collision between C 2 H 4 and [Cp-Rh-(C 2 H 4 -μH)] + forms an energy rich-adduct product, Cp-Rh(C 2 H 4 -μH)(C 2 H 4 ) + *, which undergoes the vinylic C-H cleavage.…”
Section: Introductionmentioning
confidence: 99%